2022
DOI: 10.1002/apxr.202200042
|View full text |Cite
|
Sign up to set email alerts
|

How Porosity Affects the Performance of Piezoelectric Energy Harvesters and Sensors

Abstract: Porosity has been experimentally employed to enhance the power output of piezoelectric energy harvesters. However, porosity lowers the breakdown voltage of the piezoelectric layer and hampers the pre‐poling of the piezoelectric, which is needed to achieve enhanced performance. Furthermore, the effect of fractional porosity and pore size on the poling conditions and the enhanced power output of the comprising piezoelectric harvesters is not yet known. Here, through finite‐element method simulations, it is shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…47 Previous studies demonstrated that porous materials featuring a lower modulus have improved compression deformation and also the emergence of local stress hot spots improved the output performance. 41,42,48,49 Munier et al demonstrated that the alignment of cellulose nanocrystals (CNCs) along the pore wall direction can be achieved by the unidirectional freezing of a CNC dispersion. 50 However, only a few reports are available on the preparation of anisotropic aerogels for piezoelectric applications.…”
Section: Introductionmentioning
confidence: 99%
“…47 Previous studies demonstrated that porous materials featuring a lower modulus have improved compression deformation and also the emergence of local stress hot spots improved the output performance. 41,42,48,49 Munier et al demonstrated that the alignment of cellulose nanocrystals (CNCs) along the pore wall direction can be achieved by the unidirectional freezing of a CNC dispersion. 50 However, only a few reports are available on the preparation of anisotropic aerogels for piezoelectric applications.…”
Section: Introductionmentioning
confidence: 99%